1999
DOI: 10.1021/es9809455
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Transformation of Trichloroethylene and Tetrachloroethylene by Iron Sulfide

Abstract: The transformation of trichloroethylene (TCE), tetrachloroethylene (PCE), and 1,1-dichloroethylene (1,1-DCE) by 10 g/L (0.5 m2/L) FeS in aqueous solution at pH 8.3 was studied in batch experiments. TCE and PCE were transformed by FeS with pseudo-first-order rate constants, corrected for partitioning to the sample headspace, of (1.49 ± 0.14) × 10-3 h-1 (TCE) and (5.7 ± 1.0) × 10-4 h-1 (PCE). A 17% decrease in the concentration of 1,1-DCE was observed over 120 days; however, no reaction products were detected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
235
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(263 citation statements)
references
References 31 publications
24
235
1
3
Order By: Relevance
“…Although acetylene was not detected in the aquifer, the additional occurrence of abiotic reductive dechlorination cannot be overlooked as acetylene can be further transformed to readily biodegradable compounds such as acetaldehyde, acetate and ethanol in groundwater (Liang et al, 2009). Finally, while biotically produced mackinawite may catalyze abiotic reductive dechlorination of PCE and TCE (Butler and Hayes, 1999), it was shown that cDCE was not reactive with mackinawite (Jeong et al, 2011). Abiotic reductive cDCE dechlorination is thus not likely to take place in the presence of mackinawite, though biotically produced nonmeasurable surface-bound Fe(II) (Han et al, 2012) and other reduced iron minerals such as green rust (Lee and Batchelor, 2002b) may induce such a reaction.…”
Section: Evolution Of Chlorinated Ethene Concentrationsmentioning
confidence: 99%
“…Although acetylene was not detected in the aquifer, the additional occurrence of abiotic reductive dechlorination cannot be overlooked as acetylene can be further transformed to readily biodegradable compounds such as acetaldehyde, acetate and ethanol in groundwater (Liang et al, 2009). Finally, while biotically produced mackinawite may catalyze abiotic reductive dechlorination of PCE and TCE (Butler and Hayes, 1999), it was shown that cDCE was not reactive with mackinawite (Jeong et al, 2011). Abiotic reductive cDCE dechlorination is thus not likely to take place in the presence of mackinawite, though biotically produced nonmeasurable surface-bound Fe(II) (Han et al, 2012) and other reduced iron minerals such as green rust (Lee and Batchelor, 2002b) may induce such a reaction.…”
Section: Evolution Of Chlorinated Ethene Concentrationsmentioning
confidence: 99%
“…From laboratory studies with pure minerals, acetylene is the primary end product of CAH dechlorination (Butler and Hayes, 1998, 1999Gander et al, 2002;Lee and Batchelor, 2002). However, acetylene may not be useful as an indicator of abiotic dechlorination in live systems as it is labile and certainly transient.…”
Section: Bird Backgroundmentioning
confidence: 99%
“…FeS minerals are strongly reduced and facilitate the autoreduction of CAH compounds similar to exposure to elemental iron. Synthetic FeS has been documented to dechlorinate a wide range of chlorinated compounds including PCE, TCE, PCA, CT, PCA, and others (Butler and Hayes, 1998, 1999Gander et al, 2002). Lee and Batchelor (2002) also found good dechlorination rates for PCE, cDCE, and VC by reaction with pyrite (FeS 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact pathway has not been fully determined, it is thought that the pathway for TCE oxidation is via the cis-dichlorovinyl radical directly to acetylene (Butler and Hayes, 1999). Because acetylene is unstable and very transient, it is hard to detect.…”
Section: Acetylenementioning
confidence: 99%